Design of a current-ripple-based controller for integrated DC-DC converters - Xie, Yanshan (Nanyang Technological University, 2022)
Power management ICs (PMICs) are essential in portable electronic devices to manage the voltage conversion and regulation, and often employ DC-DC converters due to the high power-efficiency of these converters. In small form-factor portable applications where size is paramount, there is an increasing trend of operating the DC-DC converter at high frequencies (>10 MHz) to shrink the size of the required inductor so that the inductor can be integrated monolithically or within the semiconductor package of the PMIC. Nonetheless, compared to the external (discrete) inductors, the integrated inductors can have higher variations that degrade the steady-state stability and the transient response of the converters. To compensate for the variation, algorithms for auto-tuning the control loop are employed in digitally-controlled DC-DC converters, but these algorithms are often computationally complex and require significant hardware circuities that are power-inefficient for the high-frequency operation. Hence, there is a need for a digital controller that can yield stable steady-state and satisfactory transient response performance despite the variation in the integrated inductor, yet simple for realization in high-frequency DC-DC converters.